2021
DOI: 10.2174/1871530321666201230111911
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Cancer and Nodules in Graves’ Disease: A Single Center Experience

Abstract: Background: The existence of a link between Graves’ Disease (GD) and Thyroid Cancer (TC) has long been investigated, however a clear pathogenic correlation has still to be found. Methods: In this study we analyzed retrospectively a cohort of 151 patients treated at our Clinic with total thyroidectomy between 2013 and 2018. All patients were symptomatic at the time of surgery, preoperatively ultrasonographic (US) study was performed to evaluate the presence of nodules and their distribution. All patients reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The finding of thyroid papillary carcinoma affecting three patients in our cohort was unexpected. In fact, papillary thyroid cancer is rare and it has been shown to be more common in people who have Graves' disease 33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding of thyroid papillary carcinoma affecting three patients in our cohort was unexpected. In fact, papillary thyroid cancer is rare and it has been shown to be more common in people who have Graves' disease 33 …”
Section: Discussionmentioning
confidence: 99%
“…In fact, papillary thyroid cancer is rare and it has been shown to be more common in people who have Graves' disease. 33 With regard to PRD, 15 out of 41 (36.6%) patients who underwent an ophthalmic screening were found to manifest signs of this retinal dystrophy. Of note, 4 of the 15 patients with PRD have been previously described by Mahroo et al 16 The term PRD is a historic one, used to describe a retinal phenotype that is characterized by foci of pigment deposition in the retina.…”
Section: Extramuscular Comorbiditiesmentioning
confidence: 99%
“…Unlike most previous studies investigating the prevalence of thyroid cancer in GD patients who underwent thyroidectomy, the present study enrolled all GD patients with thyroid cancer who were treated at three tertiary hospitals. Data from previous studies regarding the prevalence of coexisting thyroid cancer in GD patients assessed preoperatively by US are summarized in Supplemental Table S2 [9,16,[22][23][24][25][26][27][28][29][30]. Studies using US to find thyroid nodules reported varying rates of concomitant thyroid cancer in GD patients were reported (3.3% to 28.2%).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of PTC in GD has been increasing overtime and the rate of cancer in GD is higher when compared to euthyroid controls [4,6,7,13]. The possible mechanism behind remains to be elucidated, some studies report that antibodies may be the reason behind this association.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of PTC has increased worldwide and most recently reported to be 2-17% [4]. Malignancy rate of palpable thyroid nodules in GD patients has reported to be as low as 2.3% to up to 45.8% [5].…”
Section: Introductionmentioning
confidence: 99%